Short-Term Effects of Pressure Controlled Versus Volume Controlled Noninvasive Ventilation in Subjects With Amyotrophic Lateral Sclerosis. - Crescimanno, Grazia; Greco, Francesca; Bertini, Manuela; Arrisicato, Salvo; Marrone, Oreste (Respiratory Care, 2021)
BACKGROUND: Comparison of the effects of pressure controlled and volume controlled noninvasive ventilations (NIV) has usually been limited to the degree of improvement in blood gases. We compared sleep quality, abnormal respiratory events, and patient-ventilator asynchronies during administration of pressure controlled continuous mandatory ventilation (PC-CMV) and volume controlled continuous mandatory ventilation (VC-CMV) in subjects with amyotrophic lateral sclerosis naive to NIV after titration aimed at maximally improving nocturnal arterial blood gases. METHODS: A crossover evaluation of PC-CMV and VC-CMV was performed in 27 subjects with amyotrophic lateral sclerosis. After baseline polysomnography, ventilators were set in random order so as to warrant similar and satisfactory oxygen saturation and transcutaneous PCO2 in both NIV modalities during day and night. Soon after titration, polysomnography was repeated during administration of each type of NIV. RESULTS: With respect to the baseline night, non-rapid eye movement 3, and rapid eye movement sleep stages increased, and the arousal index decreased during PC-CMV (P = .005, P = .02, and P = .01, PC-CMV vs VC-CMV, respectively) but not during VC-CMV. The arousal index during NIV was correlated to the peak pressure delivered by the ventilators (p = 0.47, P < .001). Few abnormal respiratory events were observed in both NIV modes. Patient-ventilator asynchronies were more frequent during VC-CMV (median [IQR] 20.8 [0.0 - 22.0] vs 31.8 [30.1 - 34.0] no./h, PC-CMV vs VC-CMV; P = .002). Twenty-one subjects declared that they preferred PC-CMV therapy. CONCLUSIONS: In the short term, PC-CMV may be a preferred NIV modality to VC-CMV for patients with amyotrophic lateral sclerosis, even when both NIV modes are similarly effective in the correction of hypoventilation. Evaluation of the effectiveness of NIV should not be limited to the assessment of blood gas correction.